The GTAP-W model: Accounting for water use in agriculture - Alvaro Calzadilla; Katrin Rehdanz; Richard S.J. Tol (Kiel Institute for the World Economy (IfW), 2011)
Water and agriculture are intrinsically linked. Water is essential for crop production and agriculture is the largest consumer of freshwater resources. However, this link is commonly ignored by economic models mainly because water use is not reported in the national economic accounts. Few regions have markets for water. This paper describes the new version of GTAP-W, a multi-region, multi-sector computable general equilibrium model of the world economy. The new version of GTAP-W distinguishes between rainfed and irrigated agriculture and introduces water as an explicit factor of production for irrigated agriculture. Moreover, the new production structure accounts for substitution possibilities between irrigation and other primary factors. The new model has been used to study a variety of topics including: irrigation efficiency, sustainable water use, climate change and trade liberalization. This paper is a technical description of the data and features added to the standard GTAP model.
Keywords: D58; Q17; Q25; 330; computable general equilibrium; irrigation; water policy; Bewässerung; Wasserversorgung; Landwirtschaft; Wasserpolitik; Allgemeines Gleichgewicht; Mehr-Länder-Modell; Mehr-Sektoren-Modell; Theorie